2022
DOI: 10.1007/s13753-022-00419-0
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Risk Resilience: Conceptual Evolution, Key Issues, and Opportunities

Abstract: Resilience has become a cornerstone for risk management and disaster reduction. However, it has evolved extensively both etymologically and conceptually in time and across scientific disciplines. The concept has been (re)shaped by the evolution of research and practice efforts. Considered the opposite of vulnerability for a long time, resilience was first defined as the ability to resist, bounce back, cope with, and recover quickly from the impacts of hazards. To avoid the possible return to conditions of vuln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…The value of activating heterogeneous and distributed networks throughout the territory is recognized, promoting the free exchange of knowledge and skills between the different communities that define their ERD. In this sense, participatory citizenship is related to "resilience" (Graveline & Germain, 2022) since the process allows people to learn together, supporting experimentation and increasing the potential for (social and technological) innovation (Jeans et al, 2016). Some achievements in the process include identifying the specificities and situated needs of the territories, interpreting the socially diverse realities, and developing solutions consistent with the requirements of the communities the ERD will address.…”
Section: Resultsmentioning
confidence: 99%
“…The value of activating heterogeneous and distributed networks throughout the territory is recognized, promoting the free exchange of knowledge and skills between the different communities that define their ERD. In this sense, participatory citizenship is related to "resilience" (Graveline & Germain, 2022) since the process allows people to learn together, supporting experimentation and increasing the potential for (social and technological) innovation (Jeans et al, 2016). Some achievements in the process include identifying the specificities and situated needs of the territories, interpreting the socially diverse realities, and developing solutions consistent with the requirements of the communities the ERD will address.…”
Section: Resultsmentioning
confidence: 99%
“…3 eleven aspects of resilience are a series of dimensions, properties, and outcomes that form one of the frameworks. Previous research has shown the importance of using resilience frameworks for disaster risk management [59]. For example, research has demonstrated that using resilience frameworks can help to improve the resilience of urban areas to disasters and reduce the impact of disasters on critical infrastructure [60].…”
Section: Framework For Assessing Resiliencementioning
confidence: 99%
“…Strategizing against disasters is the prior objective of most nations in an attempt to adopt a proactive approach to disasters instead of a reactive one. In 2017 alone, more than 200 papers were published on resilience in the field of risk and disaster management, a sevenfold increase from 10 years earlier (Graveline & Germain, 2022). The spectre of natural disasters looms large, often striking with devastating consequences, especially in vulnerable communities.…”
Section: Introductionmentioning
confidence: 99%